Colorectal cancer diagnosed during pregnancy: systematic review and treatment pathways. Issue 7 (July 2017) - Pellino, Gianluca; Simillis, Constantinos; Kontovounisios, Christos; Baird, Daniel L.; Nikolaou, Stella; Warren, Oliver; Tekkis, Paris P.; Rasheed, Shahnawaz
Abstract : The aim of this study was to identify the mode of presentation and incidence of colorectal cancer in pregnancy (CRC-p), assess the outcomes of the mother and foetus according to gestational age, treatment delivered and cancer features and location. A systematic review of the literature was carried out to identify studies reporting on CRC-p and pooled analysis of the reported data. Seventy-nine papers reporting on 119 patients with unequivocal CRC-p were included. The calculated pooled risk is 0.002% and age at diagnosis has decreased over time. The median age at diagnosis was 32 (range, 17–46) years. Twelve per cent, 41 and 47% of CRC-p were diagnosed during the first, second and third trimester. The CRC-p site was the colon in 53.4% of cases, the rectum in 44% and multiple sites in 2.6%. Bleeding occurred in 47% of patients, abdominal pain in 37.6%, constipation in 14.1%, obstruction in 9.4% and perforation in 2.4%. Out of 82 patients whose treatment was described, 9.8% received chemotherapy during pregnancy. None of their newborns developed permanent disability, one developed hypothyroidism and 72% of newborns were alive. Vaginal delivery was possible in 60% of cases. Anterior resection was performed in 30% of patients and abdominoperineal excision of the rectum in 14.9%. Five patients had either synchronous (60%) or metachronous liver resection (40%). The median survival in these patients was 42 (0–120) months. Fifty-five per cent of patients were alive at the last available follow-up. The median survival of the mother was 36 (0–360) months. Patients with rectal cancer had longer survival compared with patients with colon cancer ( P =0.0072). CRC-p is rare, leading to symptoms being overlooked, and diagnosis made at advanced stages. Cases described in the literature include patients who had cancer before pregnancy or developed it after delivery. Survival has not increased over time and the management of these patients requires collaboration between specialties and active interaction with the patients. Abstract : Supplemental Digital Content is available in the text.